O instituto da hipoteca judiciária e a sua atual aplicabilidade no ordenamento pátrio = Judicial mortgage and its current applicability to the brazilian legal system - Barbosa, Fernanda Leal (2017)
Submitted by gsalbuqu@stj.jus.br (gsalbuqu@stj.jus.br) on 2017-04-24T18:04:21Z No. of bitstreams: 2 instituto_hipoteca_judiciaria_barbosa.pdf: 324505 bytes, checksum: 1c7eaacefde006b56883c80af810d8b8 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)